Binary Blend All‐Polymer Solar Cells with a Record Efficiency of 17.41% Enabled by Programmed Fluorination Both on Donor and Acceptor Blocks. Issue 23 (24th June 2022) - Zhou, Dehong; Liao, Chentong; Peng, Shaoqian; Xu, Xiaopeng; Guo, Yuanyuan; Xia, Jianlong; Meng, Huifeng; Yu, Liyang; Li, Ruipeng; Peng, Qiang
Abstract: Despite remarkable breakthrough made by virtue of "polymerized small‐molecule acceptor (PSMA)" strategy recently, the limited selection pool of high‐performance polymer acceptors and long‐standing challenge in morphology control impede their further developments. Herein, three PSMAs of PYDT‐2F, PYDT‐3F, and PYDT‐4F are developed by introducing different fluorine atoms on the end groups and/or bithiophene spacers to fine‐tune their optoelectronic properties for high‐performance PSMAs. The PSMAs exhibit narrow bandgap and energy levels that match well with PM6 donor. The fluorination promotes the crystallization of the polymer chain for enhanced electron mobility, which is further improved by following n ‐doping with benzyl viologen additive. Moreover, the miscibility is also improved by introducing more fluorine atoms, which promotes the intermixing with PM6 donor. Among them, PYDT‐3F exhibits well‐balanced high crystallinity and miscibility with PM6 donor; thus, the layer‐by‐layer processed PM6/PYDT‐3F film obtains an optimal nanofibril morphology with submicron length and ≈23 nm width of fibrils, facilitating the charge separation and transport. The resulting PM6/PYDT‐3F devices realizes a record high power conversion efficiency (PCE) of 17.41% and fill factor of 77.01%, higher than the PM6/PYDT‐2F (PCE = 16.25%) and PM6/PYDT‐4F (PCE = 16.77%) devices. Abstract : A series of polymerized small molecular acceptors are developed by rational fluorination on the end groups and π ‐spacers to fine‐tune the photoelectronic properties, molecular crystallinity, and miscibility with the polymer donor, which enables a record power conversion efficiency of 17.41% in layer‐by‐layer processed all‐polymer solar cells.